2018
DOI: 10.3389/fphys.2018.00487
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety and Efficacy of Wenxin Keli-Amiodarone Combination on Heart Failure Complicated by Ventricular Arrhythmia: A Systematic Review and Meta-analysis

Abstract: Objectives: To evaluate possible adverse effects and efficacy of Wenxin keli (WXKL)-amiodarone combination on heart failure complicated by ventricular arrhythmia.Methods: Nine electronic literature databases (the Cochrane Library, PubMed, EMBASE, IPA, AMED, CBM, CNKI, VIP, and WanFang) were searched up to February 2018. Two authors extracted data and assessed risk of bias of the included studies independently. Randomized controlled trials (RCTs) and quasi-RCTs about WXKL-amiodarone combination and amiodarone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…WXKL prevented dysregulation of the I NaL , sodium-calcium exchanger current (I NCX ) and Ca 2+ overload induced by ischemia-reperfusion and protected cardiomyocytes from arrhythmia and death (Luo et al, 2017). Some clinical studies have found that WXKL can reduce heart rate, improve heart failure, and relieve heart failure complications (Zheng et al, 2018;Chen et al, 2014). Shensong Yangxin (SSYX) is composed of extracts from 12 herbs, including Panax ginseng, Ophiopogon japonicus, Cornus officinalis, etc.…”
Section: Arrhythmiamentioning
confidence: 99%
“…WXKL prevented dysregulation of the I NaL , sodium-calcium exchanger current (I NCX ) and Ca 2+ overload induced by ischemia-reperfusion and protected cardiomyocytes from arrhythmia and death (Luo et al, 2017). Some clinical studies have found that WXKL can reduce heart rate, improve heart failure, and relieve heart failure complications (Zheng et al, 2018;Chen et al, 2014). Shensong Yangxin (SSYX) is composed of extracts from 12 herbs, including Panax ginseng, Ophiopogon japonicus, Cornus officinalis, etc.…”
Section: Arrhythmiamentioning
confidence: 99%
“…Based on a systematic review and meta-analysis on 13 studies published in Chinese, WXKL plus amiodarone combination group was shown to be superior in total effective rate, heart function and reduction in PVCs compared to amiodarone alone. WXKL downregulates genes associated with inflammation, neurohumoral system and apoptosis (53,54).…”
Section: Effects Of Wxkl On Ventricular Electrophysiologymentioning
confidence: 99%
“…Notably, fangjis prescriptions have a long history of use and their effectiveness has been previously verified in clinical settings (7)(8)(9). Fangjis possess "multitarget, multipathway" traits, which are not only beneficial in combatting complex diseases and flexible phenotypes, but also allow personalized treatment plans to be designed in accordance with genetic characteristics of an individual patient.…”
Section: Introductionmentioning
confidence: 99%